COMPARISON OF INDICATOR KRIGING AND CONDITIONAL SIMULATION APPLIED TO SPATIAL DISTRIBUTION OF THE VECTOR AEDES AEGYPTI - GARCÊZ, Ana Cristina Alves; DE MELLO, Marcello Neiva; RAMOS, Edson Marcos Leal Soares; PROTÁZIO, João Marcelo Brazão; FARIAS, Paulo Roberto da Silva (Brazilian Journal of Biometrics, 2017)
This study was conducted to evaluate the spatial distribution of Aedes aegypti and to compare estimation methods of indicator kriging and conditional simulation. It was collected data from both dry and rainy periods through home visits and inspection of water contained in deposits in two areas (Train and New City) of the city of Macapá, Brazil. Among the main findings, it could be highlighted that the highest incidence of larvae was observed in the rainy season. It was also observed that, in both neighborhoods, the exponential model presented the best fit to the data. This model was used in the indicative kriging estimation method. It was applied descriptive measures such as mean, standard deviation and coefficient of variation for comparing observed and estimated values obtained by kriging and conditional simulation. The results showed that the conditional simulation was the best method for estimating the spatial distribution of Aedes aegypti in the two study areas.